An ultrasensitive method for the quantitation of active and inactive GLP-1 in human plasma via immunoaffinity LC–MS/MS. (January 2014) - Chappell, Derek L; Lee, Anita YH; Castro-Perez, Jose; Zhou, Haihong; Roddy, Thomas P; Lassman, Michael E; Shankar, Sudha S; Yates, Nathan A; Wang, Weixun; Laterza, Omar F
Background: Measuring endogenous levels of incretin hormones, like GLP-1, is critical in the development of antidiabetic compounds. However, the assays used to measure these molecules often have analytical issues.Results: We have developed an ultrasensitive, highly-selective immunoaffinity LC–MS/MS (IA LC–MS/MS) assay capable of quantitating endogenous levels of active (7–36 amide) and inactive (9–36 amide) GLP-1 in human plasma. We performed fit-for-purpose validation of the assay by assessing the following assay performance characteristics: inter-assay precision, sensitivity, spike recovery, dilution linearity, absolute recovery, matrix effect, immunoprecipitation efficiency, and food effect.Conclusion: We have developed a robust analytical method for the quantitation of endogenous active and inactive GLP-1 in human plasma. In addition, we employed this method to measure the typical changes in GLP-1 levels after food intake. The sensitivity of this assay is better than another LC–MS/MS GLP-1 assay previously reported and many commercially available immunoassays. This important analytical tool could be used to qualify and/or harmonize the different immunoassays used for the quantitation of GLP-1.